No Evidence for Intercohort Cannibalism in Mixed-Size Cultures of Food-Size and Fingerling Channel Catfish × Blue Catfish Hybrids Grown in Ponds. (2nd January 2016) - Torrans, Les; Ott, Brian
Abstract: Female Channel Catfish Ictalurus punctatus × male Blue Catfish I. furcatus hybrids are normally harvested by seining single-batch pond or split-pond production systems in fall or winter. Ponds are typically restocked with fingerlings without draining. There is concern that without completely draining the pond after harvest, food-size hybrids that escape seining may cannibalize restocked fingerlings. The purpose of this study was to determine if such hybrid fingerlings stocked after the fall harvest would be cannibalized by the larger carryover fish during winter or the following growing season. Three 0.04-ha ponds were each stocked on November 25, 2013, with 100 food-size hybrid catfish averaging 1.07 kg. Those three ponds and an additional three ponds were then stocked on November 27, 2013, with 300 hybrid catfish fingerlings averaging 14.8 g. The fish were not fed over winter. Mean survival of the fingerlings after 4 months at 91.9% and 92.9% was not significantly different between treatments. Survival of the food-size fish was 99.7%. Four ponds stocked with fingerling and food-size hybrids and an additional four ponds stocked with just fingerlings in April 2014 were harvested in October. Survival of the fingerlings was not significantly different between ponds with (88.8%) and without (90.3%) food-size fish. We found no significant intercohort cannibalism by food-size hybrid catfish on understocked fingerlings either overwinter or during the following growing season. Received June 8, 2015; accepted September 9, 2015